N-Substituted Phenothiazines as Environmentally Friendly Hole-Transporting Materials for Low-Cost and Highly Stable Halide Perovskite Solar Cells - Salunke, Jagadish (ACS Omega, 2020)
[Image: see text] Most of the high-performing halide perovskite solar cells (PSCs) leverage toxic chlorinated solvents (e.g., o-dichlorobenzene or chlorobenzene) for the hole-transporting material (HTM) processing and/or antisolvents in the perovskite film fabrication. To minimize the environmental and health-related hazards, it is highly desirable, yet at the same time demanding, to develop HTMs and perovskite deposition processes relying on nonhalogenated solvents. In this work, we designed two small molecules, AZO-III and AZO-IV, and synthesized them via simple and environmentally friendly Schiff base chemistry, by condensation of electron-donating triarylamine and phenothiazine moieties connected through an azomethine bridge. The molecules are implemented as HTMs in PSCs upon processing in a nonchlorinated (toluene) solvent, rendering their synthesis and film preparation eco-friendly. The enhancement in the power conversion efficiency (PCE) was achieved when switching from AZO-III (9.77%) to AZO-IV (11.62%), in which the thioethyl group is introduced in the 2-position of the phenothiazine ring. Additionally, unencapsulated PSCs based on AZO-III displayed excellent stabilities (75% of the initial PCEs is retained after 6 months of air exposure for AZO-III to be compared with a 48% decrease of the initial PCE for Spiro-OMeTAD-based devices). The outstanding stability and the extremely low production cost (AZO-III = 9.23 $/g and AZO-IV = 9.03 $/g), together with the environmentally friendly synthesis, purification, and processing, make these materials attractive candidates as HTMs for cost-effective, stable, and eco-friendly PSCs.